Mathematical Modeling of Epidemic Spread: Predicting and ‎Controlling Infectious Diseases - Pushparajesh , V.; Singh , Jagtej; Kaushik , Dr. Naresh; Parhi , Dr. Manoranjan; Singh , Harshit; Nandhini, Dr. S. Usha; Arora‎, Arpit (International Journal of Basic and Applied Sciences, 2025)
Infectious diseases spread between individuals through direct or indirect contact. Microparasites, such as viruses and bacteria, and ‎macroparasites, including flukes and helminths, are primarily responsible for causing a wide range of infectious diseases. Ecological and ‎climatic changes increase the risk of pathogen emergence. Moreover, the evolution of pathogens makes it difficult to predict the spatio-temporal invasion of the diseases. HIV, smallpox, rabies, measles, dengue, and cholera are some of the diseases. For decades, these diseases ‎have emerged: Zika, Ebola, Chikungunya, and others. Recently, these invaders have spread widely across the globe in just a few months. ‎Infectious diseases can be a major economic problem for poor nations. Neglected tropical diseases lead to physical impairments and early ‎deaths that hinder a nation's economic growth. Human-caused diseases harm both humans and animals, affecting economies and agriculture. ‎Avian flu, foot-and-mouth disease, and viruses causing hemorrhage in fish all fall under this category of diseases. Because of significant ‎financial damages in food production, farming industries, and the fisheries sectors annually. Furthermore, pathogens spread between species ‎such as animals, birds, etc. Create the chance for humans to get sick‎.
Keywords: Epidemic; Infection; Disease; Mathematical Model